Medical Management of Chronic Pancreatitis in Children: A Position Paper by the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition Pancreas Committee. Issue 2 (February 2021) - Freeman, A. Jay; Maqbool, Asim; Bellin, Melena D.; Goldschneider, Kenneth R.; Grover, Amit S.; Hartzell, Cheryl; Piester, Travis L.; Szabo, Flora; Kiernan, Bridget Dowd; Khalaf, Racha; Kumar, Rakesh; Rios, Mirta; et al.
Abstract : ABSTRACT: This position paper summarizes the current understanding of the medical management of chronic pancreatitis (CP) in children in light of the existing medical literature, incorporating recent advances in understanding of nutrition, pain, lifestyle considerations, and sequelae of CP. This article complements and is intended to integrate with parallel position papers on endoscopic and surgical aspects of CP in children. Concepts and controversies related to pancreatic enzyme replacement therapy (PERT), the use of antioxidants and other CP medical therapies are also reviewed. Highlights include inclusion of tools for medical decision-making for PERT, CP-related diabetes, and multimodal pain management (including an analgesia ladder). Gaps in our understanding of CP in children and avenues for further investigations are also reviewed.